2021
DOI: 10.1038/s41598-021-89144-0
|View full text |Cite
|
Sign up to set email alerts
|

High loading of trimethylglycine promotes aqueous solubility of poorly water-soluble cisplatin

Abstract: Trimethylglycine (TMG) is a cheap, natural, and highly biocompatible compound. Therefore, it has been used in the fields of food and life sciences, but the application of solid TMG is limited to utilisation as an “additive”. In the present study, we focussed on the high solubility of TMG in water, derived from the aprotic zwitterionic structure, and proposed TMG as the chemical accounting for a major portion of the aqueous solution (e.g., 50 wt%). High loading of TMG shifted the properties of water and enabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Trimethylglycine. Kadokawa et al 35 reported that a highly concentrated solution of trimethyl glycine (TMG, also known as betaine) is able to improve the solubility of cisplatin in water without affecting the pharmacological proprieties of this drug. The mechanism behind this effect seems to lie in the hydrogen bond acceptor property of the carboxylate of TMG, which establishes hydrogen bonds with the amino groups of cisplatin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Trimethylglycine. Kadokawa et al 35 reported that a highly concentrated solution of trimethyl glycine (TMG, also known as betaine) is able to improve the solubility of cisplatin in water without affecting the pharmacological proprieties of this drug. The mechanism behind this effect seems to lie in the hydrogen bond acceptor property of the carboxylate of TMG, which establishes hydrogen bonds with the amino groups of cisplatin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This study of all procedures for CP-LPS and β-CD-CP-LPS was fulfilled in an ordinary method. The solubility of CP is 2.5 mg in 1 mL of water at 30 ℃, approximately and the solubility of CP can increase to 4 mg in 1 mL of water at 35 ℃ [15,16]. Nevertheless, in part of ultrasonic sonication, liposomal preparation increased the temperature to 40 ℃.…”
Section: Discussionmentioning
confidence: 99%
“…The liposomal NVs were kept in transparent vials and stored at room temperature 30 ± 2, 45 ± 2 and containing the drug-loaded vesicles were analyzed with UV spectroscopy (Perkin Elmer Lambda Bio UV/Vis Spectrometer) at 301 nm [15][16][17][18].…”
Section: Stability Of Cp-lps Dispersionmentioning
confidence: 99%
See 2 more Smart Citations